Investment Committees and Corporate Cash Holdings - Al-Hadi, Al-Hadi Ahmed; Eulaiwi, Baban; Al-Yahyaee, Khamis; Duong, Lien; Taylor, Grantley (ELSEVIER SCIENCE INC, 2020)
We investigate the association between the voluntary formation of a board investment committee (IC) and corporate cash holdings for a large sample of Gulf Cooperation Council (GCC) firms over the 2005–2013 period. We provide evidence that the existence of a specialized IC increases corporate cash holdings. We also find that several IC characteristics, i.e., member experience, independence, number of meetings, and committee size, are associated with an increase in firms’ cash holdings. Furthermore, the local and foreign institutional ownership of GCC firms moderates the IC-cash holdings relationship. These results remain robust to alternative specifications of cash holdings and endogeneity tests. We contribute to the literature on firms’ incentives to hold cash and to the literature on governance in emerging market contexts.